Agricultural price policy in India - Satish Chandra (Allahabad, 1985)
In a viable economy like that of India, agricultural price policy is of great significance in the scheme of planned objectives of eradication of pverty and faster growth rate of the economy to materialise in quicker increase in the production capacity and thereby getting progressive standard of living particularly for the rural poor which is vitally significant.
Keywords: Prices